Changes across 66°W, the Caribbean Sea and the Western boundaries of the North Atlantic Subtropical Gyre - Casanova-Masjoan, M.; Joyce, T. M.; Perez Hernandez, Maria Dolores; Vélez Belchí,Pedro; Hernández-Guerra, A. (Progress in Oceanography, 2018)
A World Ocean Circulation Experiment Hydrographic Program along with a Global Repeat Hydrography Program occupied sections along 66°W in the North West Atlantic Ocean in 2003 and 2012. Hydrographic variables, tracers and LADCP measurements were collected in situ. This section together with the North American and South American Coasts create a closed volume, excluding any flow through the Panama Canal. Combining mass, silica and LADCP information with constraints in an inverse box model we obtain a strong eastward flow of the Gulf Stream (100.1 ± 4.6 Sv in 2003 and 123.8 ± 4.4 Sv in 2012), and westward flows of the Caribbean Current (−24.4 ± 1.0 Sv in 2003 and −24.2 ± 1.1 Sv in 2012) and Deep Western Boundary Current (DWBC). The DWBC carries the ventilated waters of the Labrador Sea and the Nordic Seas. Comparing the results of 2003 and 2012, an insignificant reduction is observed in the DWBC transport (−17.3 ± 2.9 Sv and −15.0 ± 2.5 Sv for 2003 and 2012, respectively). The net heat fluxes do not show major changes through the section during both cruises (−0.23 ± 0.08 PW in 2003 and −0.21 ± 0.12 PW in 2012). In contrast, freshwater fluxes present positive values in the dry season (0.24 Sv in spring 2012) and negative values in the wet season (−0.32 Sv in fall 2003). The difference between both cruises may be due to seasonal variability in the area.